MODIFICATION OF ECONOMIC EDUCATION DURING THE PERIOD OF RENEWAL OF THE METHODOLOGY OF TEACHING ECONOMIC SUBJECTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article presents new concepts about the process of improving the methodology of teaching economic subjects and improving the quality of students' economic knowledge, presents an author's list of methods of teaching economic subjects. The following research methods were used: formalized method of analysis and analysis of methodological developments, systematization and synthesis of data.